2013
DOI: 10.1038/srep02786
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of GDNF-expressing mesenchymal stem cells protects against MPTP-induced damage in cynomolgus monkeys

Abstract: Glial cell-derived neurotrophic factor (GDNF) has shown beneficial effects in models of Parkinson's disease. The mild results observed in the double-blind clinical trial by intraputamenal infusion of recombinant GDNF proteins warrant a search for alternative delivery methods. In this study, we investigated the function of autologous mesenchymal stem cells (MSCs) expressing GDNF (GDNF-MSCs) for protection against MPTP-induced injury in cynomolgus monkeys. MSCs were obtained from the bone marrow of individual mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…By bypassing some ethical and immunological barriers, several studies reported both a neuroprotective and a restorative effect in PD animal model [61][62][63]. On a behavioral point of view, GDNF delivery was accompanied with a significant improvement of the parkinsonian symptoms in monkey MPTP models [55,57,61,64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By bypassing some ethical and immunological barriers, several studies reported both a neuroprotective and a restorative effect in PD animal model [61][62][63]. On a behavioral point of view, GDNF delivery was accompanied with a significant improvement of the parkinsonian symptoms in monkey MPTP models [55,57,61,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, the potential of cell therapies as treatments for PD has been extensively investigated [55][56][57][58][59][60][61] with often disappointing results and limitations. By bypassing some ethical and immunological barriers, several studies reported both a neuroprotective and a restorative effect in PD animal model [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…fVM grafts performed either in the CdN or in the putamen induce increased TH innervation of the non-grafted ipsilateral nucleus , suggesting that they could potentially extend long neurites. However, direct innervation of the remote striatum from SN grafts has not been observed in these species (Collier et al, 2002;Daadi et al, 2012;Emborg et al, 2013a;Ren et al, 2013;Bloch et al, 2014).…”
Section: Axonal Outgrowth and Migration In The Host Brainmentioning
confidence: 99%
“…EGFP+ and TH+ double-labeled cells were found in SN of all grafted groups, with higher proportion in grafted group with NSCs expressing hTH (no values reported for cell counts). Some years later, MSCs modified or not to express GDNF were grafted unilaterally in CdN, Put and SN (∼ 5.2 × 10 6 cells per site) of cynomolgus monkeys (Ren et al, 2013). MPTP intoxication was performed 2 weeks after grafts (0.1 mg kg −1 IV) until animals displayed stable scores (moderate to severe, 10-14 on the PPRS) and bilateral upper limb function was assessed through a food retrieval task.…”
Section: Impact Of the Immune Status Of The Host Brainmentioning
confidence: 99%
“…37) Autologous transplantation of mesenchymal stem cells expressing GDNF in a cynomolgus monkey model of Parkinson's disease improved the motor performance and protected the dopaminergic neurons in the striatum. 38) Adeno-associated viral vector-mediated gene delivery of GDNF or BDNF provided significant neuroprotection of striatal interneurons in a quinolic acid lesion model of Huntington's disease. 39) As shown above, single or combination treatment of trophic factors or their receptor agonists seems to be a promising strategy for neuroprotection against neurodegenerative disorders and CNS injuries.…”
Section: Trophic Factorsmentioning
confidence: 99%